2023
DOI: 10.3390/ma16124425
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Drying Process for the Fabrication of Collagen-Based Sponges as Medical Devices in Biomedical Engineering

Chrysoula Katrilaka,
Niki Karipidou,
Nestor Petrou
et al.

Abstract: This paper presents a systematic review of a key sector of the much promising and rapidly evolving field of biomedical engineering, specifically on the fabrication of three-dimensional open, porous collagen-based medical devices, using the prominent freeze-drying process. Collagen and its derivatives are the most popular biopolymers in this field, as they constitute the main components of the extracellular matrix, and therefore exhibit desirable properties, such as biocompatibility and biodegradability, for in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 194 publications
(262 reference statements)
1
2
0
Order By: Relevance
“…Highly porous hydrogels can be produced using various methods, such as freeze-drying. The variation in the parameters of the freeze-drying procedure made it possible to control the microarchitecture of the porous biopaper and optimize the pore size for the intended application [33]. In accordance with many authors, our results demonstrated the major impact of freezing temperature and cooling rate on the porous structure of the scaffold, which is conditioned by the nucleation of ice [34,35].…”
Section: Discussionsupporting
confidence: 87%
“…Highly porous hydrogels can be produced using various methods, such as freeze-drying. The variation in the parameters of the freeze-drying procedure made it possible to control the microarchitecture of the porous biopaper and optimize the pore size for the intended application [33]. In accordance with many authors, our results demonstrated the major impact of freezing temperature and cooling rate on the porous structure of the scaffold, which is conditioned by the nucleation of ice [34,35].…”
Section: Discussionsupporting
confidence: 87%
“…Collagen-based scaffolds were also associated with inflammation, but to a lesser degree (13)(14)(15). Another contentious matter regarding the utilization of biomaterials is their capacity to stimulate angiogenesis and achieve vascularization (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Nanofibers for innovative medical dressings manufactured using the electrospinning technique must fulfill several requirements: to absorb excess exudates, provide and maintain a moist environment or an adequate water vapor transmission rate, possess smaller pores compared to fibers produced using traditional methods, exhibit good cellular adhesion to support cell proliferation, and enhance the healing process. Nonetheless, there is evidence that the use of inflammable liquids with high shear strength and voltage can potentially generate permanent denaturation of the collagen fibrous structure [ 28 ]. Our previous publications reported the fabrication of nanofibrous wound dressings by the electrospinning process of different protein extracts, such as collagen derived from cattle hides [ 29 , 30 ], rabbit skins [ 31 , 32 ], fish scales [ 33 , 34 ], donkey hides [ 34 ], or keratin extracted from sheep wool [ 35 ], loaded with various non-active antimicrobial agents and having advanced regenerative properties for acute and chronic wound healing.…”
Section: Introductionmentioning
confidence: 99%